Curcumin Protects against Ischemic Stroke by Titrating Microglia/Macrophage Polarization - Liu, Zongjian; Ran, Yuanyuan; Huang, Shuo; Wen, Shaohong; Zhang, Wenxiu; Liu, Xiangrong; Ji, Zhili; Geng, Xiaokun; Ji, Xunming; Du, Huishan; Leak, Rehana K.; Hu, Xiaoming (Frontiers in Aging Neuroscience, 2017)
Stroke is the most common type of cerebrovascular disease and is a leading cause of disability and death. Ischemic stroke accounts for approximately 80% of all strokes. The remaining 20% of strokes are hemorrhagic in nature. To date, therapeutic options for acute ischemic stroke are very limited. Recent research suggests that shifting microglial phenotype from the pro-inflammatory M1 state toward the anti-inflammatory and tissue-reparative M2 phenotype may be an effective therapeutic strategy for ischemic stroke. The dietary phytochemical curcumin has shown promise in experimental stroke models, but its effects on microglial polarization and long-term recovery after stroke are unknown. Here we address these gaps by subjecting mice to distal middle cerebral artery occlusion (dMCAO) and administering curcumin intraperitoneally (150 mg/kg) immediately after ischemia and 24 h later. Histological studies revealed that curcumin post-treatment significantly reduced cerebral ischemic damage 3 days after dMCAO. Sensorimotor functions—as measured by the adhesive removal test and modified Garcia scores—were superior in curcumin-treated mice at 3, 5, 7 and 10 days after stroke. RT-PCR measurements revealed an elevation of M2 microglia/macrophage phenotypic markers and a reduction in M1 markers in curcumin-treated brains 3 days after dMCAO. Immunofluorescent staining further showed that curcumin treatment significantly increased the number of CD206+Iba1+ M2 microglia/macrophages and reduced the number of CD16+Iba1+ M1 cells 10 days after stroke. In vitro studies using the BV2 microglial cell line confirmed that curcumin inhibited lipopolysaccharide (LPS) and interferon-γ (IFN-γ)-induced M1 polarization. Curcumin treatment concentration-dependently reduced the expression of pro-inflammatory cytokines, including TNF-α, IL-6 and IL-12p70, in the absence of any toxic effect on microglial cell survival. In conclusion, we demonstrate that curcumin has a profound regulatory effect on microglial responses, promoting M2 microglial polarization and inhibiting microglia-mediated pro-inflammatory responses. Curcumin post-treatment reduces ischemic stroke-induced brain damage and improves functional outcomes, providing new evidence that curcumin might be a promising therapeutic strategy for stroke.